Greta Thunberg und das Klimaproblem: wie kann eine sozial-ökologische Transformation gelingen? - Faber, Malte; Frick, Marc; Manstetten, Reiner (Discussion paper series, 2020)
With the Swedish student Greta Thunberg, the protest for the environment has taken on a personal face. Her central statement is: "Politicians are doing far too little for climate protection. This is irresponsible towards the youth." Something new has happened: Suddenly young people have become the driving force behind social-ecological change. The urge and perceived urgency to counteract environmental destruction is initially strong. Then, however, one realises that the successes seem small compared to the expectations. Over time, this perceived lack of success leads to people becoming more skeptical, less committed or even resigned. The young of today are the old of tomorrow. When youth is over, a trend towards disappointment and resignation seems inevitable. Can this be countered, and if so, how? Here it is worth drawing attention to the experiences of older people who, contrary to this trend, have shown passionate commitment throughout their lives. In order to be successful in terms of environmental policy, it is first necessary to find out what constitutes a social-ecological transformation. Once this has been clarified, older people can help the younger ones; for they can point out orientation marks for the path of a social-ecological transformation. Four of these orientation marks are examined in more detail here: (i) interdisciplinarity, (ii) time and patience, (iii) trust and (iv) public spirit. From these considerations follows a fifth message: Those who advocate social-ecological transformation must not focus solely on ecological and economic goals, but must look at society as a whole and its relationships. Preserving and promoting the public spirit is essential for the success of major changes.
Keywords: Graue Literatur